Pain management in head and neck cancer patients undergoing chemo-radiotherapy: Clinical practical recommendations. (March 2016) - Mirabile, A.; Airoldi, M.; Ripamonti, C.; Bolner, A.; Murphy, B.; Russi, E.; Numico, G.; Licitra, L.; Bossi, P.
Abstract: Pain in head and neck cancer represents a major issue, before, during and after the oncological treatments. The most frequent cause of pain is chemo/radiation related oral mucositis, which involves 80% of the patients and worsens their quality of life inhibiting speaking, eating, drinking or swallowing and sometimes reducing the treatment compliance, the maximum dose intensity and thus the potential efficacy of treatment. Nevertheless pain is still often under estimated and undertreated. An Italian multidisciplinary group of head and neck cancer specialists met with the aim of reaching a consensus on pain management in this setting. The Delphi Appropriateness method was used for the consensus. External expert reviewers evaluated the final statements. The paper contains 30 consensus-reached statements about pain management in HNC patients and offers a review of recent literature in these topics.